2008
DOI: 10.1063/1.3033547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of unintentional doped carbon on growth and properties of N-doped ZnO films

Abstract: Articles you may be interested inThermal diffusion of nitrogen into ZnO film deposited on InN/sapphire substrate by metal organic chemical vapor deposition Electrical and optical studies of metal organic chemical vapor deposition grown N-doped ZnO films Unintentional doping and compensation effects of carbon in metal-organic chemical-vapor deposition fabricated ZnO thin films The evolution of optical and electrical properties induced by rapid thermal annealing is studied on nitrogen-doped ZnO samples grown by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…The contribution of nitrogen carrier gas is not excluded on the appearance of the broad mode at 515 cm À 1 , which disappeared after annealing. Similar band was also observed by Chen et al [19] in nitrogen doped ZnO films grown by MOCVD on sapphire substrate. The second order Raman scattering appears at high frequency (1000-1200 cm À 1 ).…”
Section: Raman Spectroscopysupporting
confidence: 84%
See 3 more Smart Citations
“…The contribution of nitrogen carrier gas is not excluded on the appearance of the broad mode at 515 cm À 1 , which disappeared after annealing. Similar band was also observed by Chen et al [19] in nitrogen doped ZnO films grown by MOCVD on sapphire substrate. The second order Raman scattering appears at high frequency (1000-1200 cm À 1 ).…”
Section: Raman Spectroscopysupporting
confidence: 84%
“…N O ), and most probably the incorporation of N in the ZnO matrix, measured by SIMS, is related to defects complexes involving N. In doped samples S 1 and S 2 , or undoped film S 2 À ND grown with oxygen deficiency, the presence of defect complexes such as (N 2 ) O , CN, N 2 O, Zn-H and carbon clusters is accompanied by a breakdown of the translational symmetry that causes the well-known ZnO phonon modes to disappear. In addition, some of these complexes are known as shallow donors in ZnO and may cause easily compensation of the acceptors [19,20]. If one correlates with Hall-effect measurements presented in Table 1, this may explain the n-type conductivity and the strong electron concentration of the samples.…”
Section: Raman Spectroscopymentioning
confidence: 79%
See 2 more Smart Citations
“…Experimentally, it was reported that C sp2 clusters, which are graphite-like along grain boundaries [220,221], were found in undoped [217,222] and N-doped ZnO [216,221,222]. This indicated that defect complexes of CH x , NH x , and NC x were likely to be present [193], with C concentration significantly increasing in N-doped samples [193,223,224].…”
Section: Carbon Co-doping Effectsmentioning
confidence: 96%